Pengembangan Bahan Ajar Berbasis Liveworksheets pada Materi Kekongruenan dan Kesebangunan di Kelas IX - Mulbar, Usman; Ruldy, Faradillah; Assagaf, Said Fachry (Issues in Mathematics Education (IMED), 2024)
This research aims to develop and produce teaching materials products based on liveworksheets that are valid, practical and effective. This research method refers to a 4D development model that includes 4 stages namely define, design, development, and disseminate. The subject of this research was the grade IX UPTD SMPN 7 Barru. Research instrument in the form of validattion sheets by experts to measure validity aspect; teacher activity observation sheet and responses to measure practicality aspect; student activity observation sheet, responses, and tests to measure effectiveness aspect. The results showed that teaching materials developed had valid criteria with validity score of 3,35; practically with a score of 3,98 for the result of teacher activity observation and 90% for teacher response result; effective with a score of 82% for the result of students activity observation, 95% for student response result, and 100% for the test result.